The geography of transport systems - Rodrigue, Jean-Paul 1967 (Routledge Taylor & Francis Group, 2020)
"This expanded and revised fifth edition provides a comprehensive and accessible introduction to the field with a broad overview of its concepts, methods and areas of application. It provides an overview of the spatial aspects of transportation and focuses on how the mobility of passengers and freight is linked with geography. This volume is an essential resource for undergraduates studying transport geography, as well as those interested in economic and urban geography, transport planning and engineering. A companion web site, which contains photographs, maps, figures and PowerPoint presentations, can be found here: https://transportgeography.org/"--